Physical And Chemical Characterization Of Granitic Rock For Ree Utilization - Kamso, Nurul Syazni (Universiti Sains Malaysia, 2022)
Rare earth element (REE) is important mineral as petroleum nowadays. It is highly demand in varies field especially electronic and green technology. Granitoid and some intrusive volcanic rocks are widely spreading in Malaysia and thus, it could occupied the demand by industries and population needs as based on previous research, Malaysia’s S-type granite is rich with yttrium. The objective of this research is to analyse the mineralogy of granitic deposits by its physical and chemical characteristics. The study was conducted at Kupang, Baling District, Kedah. This geological area is known as Kupang Granite and contacted with Kroh Formation. To achieve the objective, a proper flowchart was planned by divided it into three parts which are physical characteristic, petrology characteristic and geochemical characteristic. Several methods could be conducted to achieve the objective by using polarizing microscope, X-ray diffraction (XRD), X- ray fluorescence (XRF) and Inductive Coupled Plasma Mass Spectrometer (ICP-MS). The results obtained from the visual assessment and under polarizing microscope shown the mineral exists in granite such as quartz, feldspar and biotite. XRD analysis justified the mineral existed in the thin section as all the highest peak intensity show kaolinite, quartz, albite and orthoclase. XRF analysis showing that all the samples have higher weight percent of SiO2. The major element results interpreted the type of rock by plotting on TAS diagram. ICP-MS was utilized to obtain the concentration of REE. From the observation, the REE content in all samples are quite lower that the required mineable recovery. This information can be utilized for further exploration of REE in granitic rock.